Polycarbonate composite material for 5G base station and preparation method thereof
By using polycarbonate resins with different molecular structures and molecular weights in 5G base stations for compounding, and optimizing the auxiliary group distribution ratio, the problem of insufficient signal penetration and anti-interference ability of the material is solved, and the mechanical strength, flame retardant performance and anti-aging performance of the material is improved, and it is suitable for high-demand application scenarios such as 5G base stations.
Patent Information
- Application Number
- CN202510006209.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-03
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-01-03
AI Technical Summary
The existing polymer materials for 5G base stations have shortcomings in signal penetration and anti-interference ability. Traditional polycarbonate composite materials will affect their transparency and dielectric loss after adding auxiliary components, and the processing methods have environmental protection and energy consumption problems.
By combining polycarbonate resins with different molecular structures and molecular weights, and optimizing the auxiliary group distribution ratio in the composite material, such as increasing the content of antioxidants, lubricants, tougheners, flame retardants, anti-dripping agents and anti-UV agents, to improve the mechanical strength, flame retardant and anti-aging properties of the material.
It has achieved improvements in mechanical strength, flame retardant properties and anti-aging properties of polycarbonate composite materials, while reducing the use of auxiliary components and reducing the energy consumption of materials processing, and is suitable for high-demand application scenarios such as 5G base stations.
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of polymer materials for 5G base stations, and specifically to a polycarbonate composite material for 5G base stations and a preparation method thereof. Background Art
[0002] With the continuous development of communication technology, it has put forward new demands on polymer materials in this field. The 5G signal propagation speed is extremely fast, but the penetration is low. A large number of indoor and outdoor equipment need to be laid, and the number of base stations may increase by more than 10 times. However, with the increase of communication signal rate, the adjustment of communication bands has caused the signal penetration to weaken and is susceptible to interference from external materials. This has also put forward new requirements for polymer materials used in 5G base stations. In addition to traditional high temperature resistance, flame retardant performance, mechanical strength, aging resistance, etc., related materials are also required to have characteristics including but not limited to low dielectric, low loss, high impact resistance, high heat deformation temperature, etc. Polycarbonate resin materials are currently widely used in the field of communication base stations. In order to improve the mechanical strength, heat resistance, hardness and other characteristics of traditional polycarbonate composite materials, glass fiber, PBT resin, ABS resin and other components are added. However, although the addition of auxiliary components such as these composite resins can improve the performance of certain aspects of the composite materials to a certain extent, it will also cause its transparency, dielectric loss and other characteristics to be affected. Moreover, the addition of the above-mentioned composite components will also affect the processing method of the material to a certain extent, and further improvement is needed in terms of environmental protection and energy consumption. Therefore, it is necessary to develop a polycarbonate composite material with polycarbonate resin as the base resin material and the addition of as few other components as possible, which has better comprehensive performance and can be used in 5G base stations. Summary of the invention
[0003] In response to the above technical problems, the present invention provides a polycarbonate composite material for a 5G base station, wherein polycarbonate resins with different molecular structures and different molecular weights are compounded as the base resin, and then other auxiliary components of the composite material are correspondingly optimized and adjusted, so that the polycarbonate composite material can achieve good mechanical strength, excellent flame retardant properties, aging resistance and other properties without adding other resins and adding very small amounts of auxiliary components.
[0004] Specifically, the first aspect of the present invention provides a polycarbonate composite material for a 5G base station, which is composed of the following components in parts by weight:
[0005] 90-95 parts by weight of a polycarbonate polymer;
[0006] 0.2-0.4 parts by weight of an antioxidant;
[0007] 0.5 to 1.0 parts by weight of a lubricant;
[0008] 3.0 to 5.0 parts by weight of a toughening agent;
[0009] 0.05-0.2 parts by weight of sulfonate flame retardant;
[0010] 0.3-0.5 parts by weight of an anti-dripping agent;
[0011] 1.0 to 3.0 parts by weight of an anti-UV agent;
[0012] The polycarbonate polymer comprises high molecular weight aromatic polycarbonate and aliphatic polycarbonate, the content of the high molecular weight aromatic polycarbonate in the polycarbonate polymer is not less than 30wt%; the weight average molecular weight of the high molecular weight aromatic polycarbonate is not less than 25,000.
[0013] As a preferred technical solution of the present invention, the weight average molecular weight of the high molecular weight aromatic polycarbonate is 30,000 to 52,000.
[0014] As a preferred technical solution of the present invention, the weight average molecular weight of the aliphatic polycarbonate is 20,000-60,000.
[0015] As a preferred technical solution of the present invention, the polycarbonate polymer also includes a low molecular weight aromatic polycarbonate, and the weight average molecular weight of the low molecular weight aromatic polycarbonate is not higher than 30,000; preferably, the weight average molecular weight of the low molecular weight aromatic polycarbonate is 20,000 to 30,000.
[0016] As a preferred technical solution of the present invention, the low molecular weight aromatic polycarbonate has a melt index of 7 to 13 g / 10 min at 300° C. and 1.2 kg.
[0017] As a preferred technical solution of the present invention, the weight ratio of the high molecular weight aromatic polycarbonate, the low molecular weight aromatic polycarbonate and the aliphatic polycarbonate is (3-4):5:(0.5-2).
[0018] As a preferred technical solution of the present invention, the toughening agent is MMA-grafted cross-linked silicone acrylate.
[0019] As a preferred technical solution of the present invention, the anti-UV agent is a composite of a benzotriazole anti-UV agent and a triazine anti-UV agent in equal weights.
[0020] As a preferred technical solution of the present invention, the sulfonate flame retardant is selected from one or more of potassium benzenesulfonylbenzenesulfonate, potassium perfluorobutylsulfonate, and sodium 2,4,5-trichlorobenzenesulfonate.
[0021] The second aspect of the present invention provides a method for preparing the polycarbonate composite material as described above, comprising the following steps: mixing the polycarbonate polymer, antioxidant, lubricant, sulfonate flame retardant, anti-drip agent and anti-UV agent in a mixer and then adding the mixture into a twin-screw extruder for melt extrusion to obtain the composite material.
[0022] Compared with the existing related technologies, the technical solution provided by the present invention has the following beneficial effects:
[0023] In the present invention, by adjusting the composition and ratio of the polycarbonate material in the composite material, and optimizing the flame retardant, anti-UV agent, etc., the prepared polycarbonate composite material is comprehensively improved in terms of tensile strength, flexural strength, impact strength, and anti-aging performance. In addition, the applicant also conducted a thermal deformation test on the PC alloy material in the above embodiment. The thermal deformation temperature of all materials is basically 120°C or above, and can be widely used in harsh high-temperature outdoor environments. Moreover, the content of auxiliary components in the entire material formula system does not exceed 10wt%. The composite material retains the characteristics of the polycarbonate itself as much as possible while achieving the above-mentioned modification, so that the composite material can be widely used in fields such as 5G base stations. DETAILED DESCRIPTION
[0024] When the content, dosage, or other values or parameters in the present application are expressed as a range, a preferred range, or a range defined by a series of upper preferred values and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when the range "2 to 8" is disclosed, the described range should be interpreted as including the range "2 to 8", "2 to 7", "2 to 6", "2 to 5 and 6,7", "2 to 3 and 4 to 8", etc.
[0025] When numerical ranges are described herein, unless otherwise indicated, the ranges are intended to include the endpoints and all integers and fractions within the range. The singular includes the plural unless the context clearly indicates otherwise. "Optional" or "any" means that the item or event described thereafter may or may not occur, and the description includes situations where the event occurs and situations where the event does not occur.
[0026] The polycarbonate composite material for 5G base stations provided in the present invention uses polycarbonate resins with different molecular structures and different molecular weights to be compounded as the base resin, and then other auxiliary components of the composite material are correspondingly optimized and adjusted to obtain the polycarbonate composite material of the present invention.
[0027] The polycarbonate composite material described in the present invention is composed of the following components in parts by weight:
[0028] 90-95 parts by weight of a polycarbonate polymer;
[0029] 0.2-0.4 parts by weight of an antioxidant;
[0030] 0.5 to 1.0 parts by weight of a lubricant;
[0031] 3 to 5 parts by weight of a toughening agent;
[0032] 0.05-0.2 parts by weight of sulfonate flame retardant;
[0033] 0.3-0.5 parts by weight of an anti-dripping agent;
[0034] 1 to 3 parts by weight of anti-UV agent.
[0035] The polycarbonate polymer is a PC resin material. The present invention can use polycarbonate materials known to those skilled in the art, including but not limited to bisphenol A polycarbonate, bisphenol F polycarbonate, etc., which can be prepared and used by a preparation method known to those skilled in the art, or can be obtained by commercial purchase. The specific source is not particularly limited. The polycarbonate polymer described in the present invention includes high molecular weight aromatic polycarbonate and aliphatic polycarbonate; the high molecular weight in the high molecular weight aromatic polycarbonate is only relative to other polycarbonates with relatively low molecular weight in the present application, wherein the weight average molecular weight of the high molecular weight aromatic polycarbonate is not less than 25000; the weight average molecular weight described in the present invention is a physical quantity used to measure the length of the polycarbonate molecular chain segment, which can be tested and confirmed according to methods known to those skilled in the art, including but not limited to GPC gel permeation chromatography and other methods; the aromatic polycarbonate refers to a carbonate-type high molecular weight polymer containing aromatic groups in the molecular chain; the content of the high molecular weight aromatic polycarbonate in the polycarbonate polymer described in the present invention is not less than 30wt%.
[0036] Further preferably, the weight average molecular weight of the high molecular weight aromatic polycarbonate is 30000-52000, and for example, the weight average molecular weight may be 30000, 32000, 35000, 38000, 40000, 42000, 45000, 48000, 50000, 52000, etc.; preferably, the weight average molecular weight of the high molecular weight aromatic polycarbonate is 35000-50000; in the present invention, the specific source of the high molecular weight aromatic polycarbonate meeting the above requirements is not particularly limited, and may include but are not limited to FB2560 polycarbonate material of Saudi Basic Chemicals Company, 7072R polycarbonate material of Mitsubishi Chemical of Japan, etc.
[0037] Further preferably, the weight average molecular weight of the aliphatic polycarbonate is 20000-60000, and the weight average molecular weight of the aliphatic polycarbonate can be 20000, 22000, 25000, 27000, 28000, 30000, 32000, 35000, 38000, 40000, 42000, 45000, 48000, 50000, 52000, 55000, 57000, 60000, etc.; further, the weight average molecular weight of the aliphatic polycarbonate is 30000-40000, and preferably, the aliphatic polycarbonate is selected from polypropylene carbonate resin. In the present invention, the specific source of the aliphatic polycarbonate meeting the above requirements is not particularly limited, and polypropylene carbonate resin including but not limited to Changchun Institute of Applied Chemistry can be used.
[0038] In some preferred embodiments of the present invention, the polycarbonate polymer further comprises a low molecular weight aromatic polycarbonate, wherein the low molecular weight is only relative to other polycarbonates with relatively high molecular weights in the present application; the weight average molecular weight of the low molecular weight aromatic polycarbonate is not higher than 30,000; for example, the weight average molecular weight of the low molecular weight aromatic polycarbonate is 30,000, 28,000, 25,000, 23,000, 22,000, 20,000, 18,000, 15,000, 12,000, 10,000, etc.; preferably, the weight average molecular weight of the low molecular weight aromatic polycarbonate is 20,000 to 30,000; preferably, the low molecular weight aromatic polycarbonate is molten at 300°C, 1.2k The melt index at 300°C and 1.2kg is 7-13g / 10min; the melt index at 300°C and 1.2kg is 7g / 10min, 7.5g / 10min, 8g / 10min, 8.5g / 10min, 9g / 10min, 9.5g / 10min, 10g / 10min, 10.5g / 10min, 11g / 10min, 11.5g / 10min, 12g / 10min, 12.5g / 10min, 13g / 10min and the like; in the present invention, there is no particular limitation on the specific source of the low molecular weight aromatic polycarbonate meeting the above requirements, and may include but is not limited to the A1105 polycarbonate product of Wanhua Chemical Group Co., Ltd.
[0039] In some preferred embodiments of the present invention, the weight ratio of the high molecular weight aromatic polycarbonate, the low molecular weight aromatic polycarbonate and the aliphatic polycarbonate is (3-4):5:(0.5-2); for example, the weight ratio may be 3:5:0.5, 3.5:5:0.5, 4:5:0.5, 3:5:1, 3:5:1.5, 3:5:2, 3:5:1.8, 3.5:5:0.8, 3.5:5:1.2, etc.
[0040] The polycarbonate composite material for 5G base stations of the present invention contains an antioxidant. Based on 90 to 95 parts by weight of the polycarbonate polymer, the weight of the antioxidant is 0.2 to 0.4 parts by weight. For example, the antioxidant is 0.2 parts by weight, 0.25 parts by weight, 0.3 parts by weight, 0.35 parts by weight, 0.4 parts by weight, etc.; the specific selection of the antioxidant in the present invention is not particularly limited, and can be based on antioxidants well known to those skilled in the art, including but not limited to hindered phenol antioxidants, phosphite antioxidants, thioester antioxidants, furan antioxidants, hydroxylamine antioxidants, etc., one or more combinations thereof, such as antioxidant RIANOX 245, antioxidant RIANOX 636, etc.
[0041] The polycarbonate composite material for 5G base stations of the present invention contains a lubricant. Based on 90 to 95 parts by weight of a polycarbonate polymer, the weight of the lubricant is 0.5 to 1 part by weight. For example, the weight of the lubricant is 0.5 part by weight, 0.55 part by weight, 0.6 part by weight, 0.65 part by weight, 0.7 part by weight, 0.75 part by weight, 0.8 part by weight, 0.85 part by weight, 0.9 part by weight, 0.95 part by weight, 1.0 part by weight, etc.; preferably, the lubricant is a silicone lubricant or a polymer wax lubricant, or the two can be blended and used; wherein the polymer wax can be various polymer wax components well known to those skilled in the art, such as polyethylene wax and microcrystalline wax, and can be selected and used according to the needs of those skilled in the art.
[0042] The polycarbonate composite material for 5G base stations of the present invention contains a toughening agent. Based on 90 to 95 parts by weight of the polycarbonate polymer, the weight of the toughening agent is 3 to 5 parts by weight. For example, the weight of the toughening agent is 3 parts by weight, 3.2 parts by weight, 3.5 parts by weight, 3.8 parts by weight, 4.0 parts by weight, 4.2 parts by weight, 4.5 parts by weight, 4.8 parts by weight, 5.0 parts by weight, etc.; preferably, the toughening agent includes MMA-grafted cross-linked silicone acrylate; further preferably, the toughening agent also includes an acrylate having a core-shell structure. Preferably, the MMA-grafted cross-linked silicone acrylate and the acrylate graft copolymer with a core-shell structure have the same weight. In the present application, there is no special limitation on the specific selection of the MMA-grafted cross-linked silicone acrylate and the acrylate graft copolymer with a core-shell structure, and they can be used according to products known to those skilled in the art or commercially available, such as but not limited to the MMA-grafted cross-linked silicone acrylate with the brand number LP2088 of Guangzhou Energy Innovation Materials Co., Ltd., such as KANE FM-40 core-shell structured acrylic acid graft copolymer, etc.
[0043] The polycarbonate composite material for 5G base stations of the present invention contains a sulfonate flame retardant. Based on 90 to 95 parts by weight of the polycarbonate polymer, the weight of the sulfonate flame retardant is 0.05 to 0.2 parts by weight. For example, the weight of the sulfonate flame retardant is 0.05 parts by weight, 0.06 parts by weight, 0.07 parts by weight, 0.08 parts by weight, 0.09 parts by weight, 0.10 parts by weight, 0.11 parts by weight, 0.12 parts by weight, 0.13 parts by weight, 0.14 parts by weight, 0.15 parts by weight, 0.16 parts by weight, 0.17 parts by weight. Parts, 0.18 parts by weight, 0.19 parts by weight, 0.2 parts by weight, etc.; further preferably, the sulfonate flame retardant is selected from one or more of potassium benzenesulfonylbenzenesulfonate, potassium perfluorobutylsulfonate, and sodium 2,4,5-trichlorobenzenesulfonate; further preferably, the sulfonate flame retardant is a compound of potassium benzenesulfonylbenzenesulfonate and potassium perfluorobutylsulfonate; further preferably, the weight ratio of potassium benzenesulfonylbenzenesulfonate and potassium perfluorobutylsulfonate is 1: (1-2), and the weight ratio can be 1: 1, 1: 1.2, 1: 1.5, 1: 1.8, 1: 2, etc. In the present invention, the specific source of the above-mentioned sulfonate flame retardant component is not particularly limited, and can be based on commercially available products known to those skilled in the art.
[0044] The polycarbonate composite material for 5G base stations of the present invention contains an anti-UV agent. Based on 90 to 95 parts by weight of the polycarbonate polymer, the weight of the anti-UV agent is 1 to 3 parts by weight. For example, the weight of the anti-UV agent is 1.0 parts by weight, 1.2 parts by weight, 1.5 parts by weight, 1.8 parts by weight, 2.0 parts by weight, 2.2 parts by weight, 2.5 parts by weight, 2.8 parts by weight, 3.0 parts by weight, etc.; further preferably, the anti-UV agent is a composite of equal weights of a benzotriazole anti-UV agent and a triazine anti-UV agent. For example, the benzotriazole anti-UV agent can be 2-(2'-hydroxy-3', 5'-di-tert-amylphenyl) benzotriazole, 2-(2'-hydroxy-3', 5'-di-tert-butylphenyl)-5-chlorobenzotriazole, etc.; the triazine anti-UV agent can be hydroxyphenyl-s-triazine, triazine (HPT), etc.
[0045] The polycarbonate composite material for 5G base stations of the present invention contains an anti-drip agent. Based on 90 to 95 parts by weight of polycarbonate polymer, the anti-drip agent is 0.3 to 0.5 parts by weight. For example, the anti-drip agent is 0.3 parts by weight, 0.32 parts by weight, 0.35 parts by weight, 0.38 parts by weight, 0.40 parts by weight, 0.42 parts by weight, 0.45 parts by weight, 0.48 parts by weight, 0.50 parts by weight, etc.; further preferably, the anti-drip agent is at least one of polytetrafluoroethylene powder, polytetrafluoroethylene particles and polytetrafluoroethylene masterbatch with acrylonitrile-styrene copolymer, polycarbonate or acrylonitrile-styrene-butadiene copolymer as carrier.
[0046] The preparation method of the polycarbonate composite material for 5G base stations of the present invention comprises the following steps: the polycarbonate polymer, antioxidant, lubricant, sulfonate flame retardant, anti-dripping agent and anti-UV agent are mixed in a mixer and then added to a twin-screw extruder for melt extrusion. The present invention does not specifically limit the specific process parameters and conditions in the preparation process of the composite material. The raw materials measured according to the ratio are poured into a mixer and stirred and mixed evenly, and then placed in a twin-screw extruder, the speed of the twin screw is adjusted (for example, 300rpm to 800rpm), and the temperature of each zone of the screw is set to 285 to 300°C. Other parameters can be adjusted accordingly according to actual needs based on methods well known to those skilled in the art.
[0047] The present invention is described in detail below by way of examples. It is necessary to point out here that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by professionals and technicians in this field based on the content of the present invention above still belong to the scope of protection of the present invention.
[0048] Example 1
[0049] This embodiment provides a polycarbonate composite material for a 5G base station, which is composed of the following components in parts by weight:
[0050] 95 parts by weight of a polycarbonate polymer;
[0051] 0.3 parts by weight of an antioxidant;
[0052] 0.8 parts by weight of a lubricant;
[0053] 4 parts by weight of a toughening agent;
[0054] 0.1 parts by weight of sulfonate flame retardant;
[0055] 0.4 parts by weight of an anti-drip agent;
[0056] 2 parts by weight of an anti-UV agent;
[0057] The polycarbonate polymer consists of high molecular weight aromatic polycarbonate, low molecular weight aromatic polycarbonate and aliphatic polycarbonate, and the weight ratio thereof is 3.5:5:1.5; the weight average molecular weight of the high molecular weight aromatic polycarbonate is 50,000, and the FB2560 polycarbonate material of Saudi Basic Chemicals Company is adopted; the weight average molecular weight of the low molecular weight aromatic polycarbonate is 23,000, and the melt index at 300° C. and 1.2 kg is 9 g / 10 min, and the A1105 polycarbonate product of Wanhua Chemical Group Co., Ltd. is adopted; the weight average molecular weight of the aliphatic polycarbonate is 35,000, and the polypropylene carbonate resin of Changchun Institute of Applied Chemistry is adopted; the antioxidant is the antioxidant RIANOX 245; the lubricant is the silicone lubricant FEIDIAN GM-3200; the toughening agent is composed of equal weights of MMA-grafted cross-linked silicone acrylate (the brand of Guangzhou Energetic Innovation Materials Co., Ltd. is LP2088) and an acrylate graft copolymer with a core-shell structure (KANE of Hangzhou Zhongju Chemical FM-40); the sulfonate flame retardant is composed of potassium benzenesulfonylbenzenesulfonate and potassium perfluorobutylsulfonate, with a weight ratio of 1:1.5; the anti-dripping agent is polytetrafluoroethylene powder; the anti-UV agent is composed of equal weights of benzotriazole anti-UV agent and triazine (HPT) anti-UV agent.
[0058] Example 2
[0059] This embodiment provides a polycarbonate composite material for a 5G base station, which is composed of the following components in parts by weight:
[0060] 95 parts by weight of a polycarbonate polymer;
[0061] 0.3 parts by weight of an antioxidant;
[0062] 0.8 parts by weight of a lubricant;
[0063] 4 parts by weight of a toughening agent;
[0064] 0.1 parts by weight of sulfonate flame retardant;
[0065] 0.4 parts by weight of an anti-drip agent;
[0066] 2 parts by weight of an anti-UV agent;
[0067] The polycarbonate polymer is composed of high molecular weight aromatic polycarbonate and aliphatic polycarbonate, and the weight ratio is 3.5:1.5; the weight average molecular weight of the high molecular weight aromatic polycarbonate is 50,000, and the FB2560 polycarbonate material of Saudi Basic Chemicals Company is adopted; the weight average molecular weight of the aliphatic polycarbonate is 35,000, and the polypropylene carbonate resin of Changchun Institute of Applied Chemistry is adopted; the antioxidant is the antioxidant RIANOX 245; the lubricant is the silicone lubricant FEIDIAN GM-3200; the toughening agent is composed of equal weights of MMA grafted cross-linked silicone acrylate (the brand of Guangzhou Entropy Innovation Materials Co., Ltd. is LP2088) and an acrylate graft copolymer with a core-shell structure (KANE FM-40); the sulfonate flame retardant is composed of potassium benzenesulfonylbenzenesulfonate and potassium perfluorobutylsulfonate, with a weight ratio of 1:1.5; the anti-dripping agent is polytetrafluoroethylene powder; the anti-UV agent is composed of equal weights of benzotriazole anti-UV agent and triazine (HPT) anti-UV agent.
[0068] Example 3
[0069] This embodiment provides a polycarbonate composite material for a 5G base station, which is composed of the following components in parts by weight:
[0070] 95 parts by weight of a polycarbonate polymer;
[0071] 0.3 parts by weight of an antioxidant;
[0072] 0.8 parts by weight of a lubricant;
[0073] 4 parts by weight of a toughening agent;
[0074] 0.1 parts by weight of sulfonate flame retardant;
[0075] 0.4 parts by weight of an anti-drip agent;
[0076] 2 parts by weight of an anti-UV agent;
[0077] The polycarbonate polymer is composed of high molecular weight aromatic polycarbonate and low molecular weight aromatic polycarbonate, and the weight ratio is 3.5:5; the weight average molecular weight of the high molecular weight aromatic polycarbonate is 50000, and the FB2560 polycarbonate material of Saudi Basic Chemicals Company is used; the weight average molecular weight of the low molecular weight aromatic polycarbonate is 23000, and the melt index at 300°C and 1.2kg is 9g / 10min, and the A1105 polycarbonate product of Wanhua Chemical Group Co., Ltd. is used; the antioxidant is the antioxidant RIANOX 245; the lubricant is the silicone lubricant FEIDIAN GM-3200; the toughening agent is composed of equal weights of MMA-grafted cross-linked silicone acrylate (the brand of Guangzhou Entropy Innovation Materials Co., Ltd. is LP2088) and an acrylate graft copolymer with a core-shell structure (the KANE FM-40); the sulfonate flame retardant is composed of potassium benzenesulfonylbenzenesulfonate and potassium perfluorobutylsulfonate, with a weight ratio of 1:1.5; the anti-dripping agent is polytetrafluoroethylene powder; the anti-UV agent is composed of equal weights of benzotriazole anti-UV agent and triazine (HPT) anti-UV agent.
[0078] Example 4
[0079] This embodiment provides a polycarbonate composite material for a 5G base station, which is composed of the following components in parts by weight:
[0080] 95 parts by weight of a polycarbonate polymer;
[0081] 0.3 parts by weight of an antioxidant;
[0082] 0.8 parts by weight of a lubricant;
[0083] 4 parts by weight of a toughening agent;
[0084] 0.1 parts by weight of sulfonate flame retardant;
[0085] 0.4 parts by weight of an anti-drip agent;
[0086] 2 parts by weight of an anti-UV agent;
[0087] The polycarbonate polymer is composed of low molecular weight aromatic polycarbonate and aliphatic polycarbonate, and the weight ratio is 5:1.5; the weight average molecular weight of the low molecular weight aromatic polycarbonate is 23000, and the melt index at 300°C and 1.2kg is 9g / 10min, and the A1105 polycarbonate product of Wanhua Chemical Group Co., Ltd. is adopted; the weight average molecular weight of the aliphatic polycarbonate is 35000, and the polypropylene carbonate resin of Changchun Institute of Applied Chemistry is adopted; the antioxidant is antioxidant RIANOX 245; the lubricant is silicone lubricant FEIDIAN GM-3200; the toughening agent is composed of equal weights of MMA grafted cross-linked silicone acrylate (the brand of Guangzhou Entropy Innovation Materials Co., Ltd. is LP2088) and acrylate graft copolymer with core-shell structure (KANE FM-40); the sulfonate flame retardant is composed of potassium benzenesulfonylbenzenesulfonate and potassium perfluorobutylsulfonate, with a weight ratio of 1:1.5; the anti-dripping agent is polytetrafluoroethylene powder; the anti-UV agent is composed of equal weights of benzotriazole anti-UV agent and triazine (HPT) anti-UV agent.
[0088] Example 5
[0089] This embodiment provides a polycarbonate composite material for a 5G base station, which is composed of the following components in parts by weight:
[0090] 95 parts by weight of a polycarbonate polymer;
[0091] 0.3 parts by weight of an antioxidant;
[0092] 0.8 parts by weight of a lubricant;
[0093] 4 parts by weight of a toughening agent;
[0094] 0.1 parts by weight of sulfonate flame retardant;
[0095] 0.4 parts by weight of an anti-drip agent;
[0096] 2 parts by weight of an anti-UV agent;
[0097] The polycarbonate polymer consists of high molecular weight aromatic polycarbonate, low molecular weight aromatic polycarbonate and aliphatic polycarbonate, and the weight ratio is 3.5:5:1.5; the weight average molecular weight of the high molecular weight aromatic polycarbonate is 30,000, and the 7027R polycarbonate material (weight average molecular weight 30,000) of Mitsubishi Chemical Corporation of Japan is adopted; the weight average molecular weight of the low molecular weight aromatic polycarbonate is 23,000, and the melt index at 300° C. and 1.2 kg is 9 g / 10 min, and the A1105 polycarbonate product of Wanhua Chemical Group Co., Ltd. is adopted; the weight average molecular weight of the aliphatic polycarbonate is 35,000, and the polypropylene carbonate resin of Changchun Institute of Applied Chemistry is adopted; the antioxidant is the antioxidant RIANOX 245; the lubricant is the silicone lubricant FEIDIAN GM-3200; the toughening agent is composed of equal weights of MMA-grafted cross-linked silicone acrylate (the brand of Guangzhou Energetic Innovation Materials Co., Ltd. is LP2088) and an acrylate graft copolymer with a core-shell structure (KANE of Hangzhou Zhongju Chemical FM-40); the sulfonate flame retardant is composed of potassium benzenesulfonylbenzenesulfonate and potassium perfluorobutylsulfonate, with a weight ratio of 1:1.5; the anti-dripping agent is polytetrafluoroethylene powder; the anti-UV agent is composed of equal weights of benzotriazole anti-UV agent and triazine (HPT) anti-UV agent.
[0098] Example 6
[0099] This embodiment provides a polycarbonate composite material for a 5G base station, which is composed of the following components in parts by weight:
[0100] 95 parts by weight of a polycarbonate polymer;
[0101] 0.3 parts by weight of an antioxidant;
[0102] 0.8 parts by weight of a lubricant;
[0103] 4 parts by weight of a toughening agent;
[0104] 0.1 parts by weight of sulfonate flame retardant;
[0105] 0.4 parts by weight of an anti-drip agent;
[0106] 2 parts by weight of an anti-UV agent;
[0107] The polycarbonate polymer is composed of high molecular weight aromatic polycarbonate, low molecular weight aromatic polycarbonate and aliphatic polycarbonate, and the weight ratio is 3.5:5:1.5; the weight average molecular weight of the high molecular weight aromatic polycarbonate is 50000, and the FB2560 polycarbonate material of Saudi Basic Chemicals Company is used; the weight average molecular weight of the low molecular weight aromatic polycarbonate is 23000, and the melt index at 300°C and 1.2kg is 9g / 10min, and the A1105 polycarbonate product of Wanhua Chemical Group Co., Ltd. is used; the weight average molecular weight of the aliphatic polycarbonate is 35000, and the polypropylene carbonate resin of Changchun Institute of Applied Chemistry is used; the antioxidant is antioxidant RIANOX 245; the lubricant is silicone lubricant FEIDIAN GM-3200; the toughening agent is an acrylate graft copolymer with a core-shell structure (KANE FM-40); the sulfonate flame retardant is composed of potassium benzenesulfonylbenzenesulfonate and potassium perfluorobutylsulfonate, with a weight ratio of 1:1.5; the anti-dripping agent is polytetrafluoroethylene powder; the anti-UV agent is composed of equal weights of benzotriazole anti-UV agent and triazine (HPT) anti-UV agent.
[0108] Example 7
[0109] This embodiment provides a polycarbonate composite material for a 5G base station, which is composed of the following components in parts by weight:
[0110] 95 parts by weight of a polycarbonate polymer;
[0111] 0.3 parts by weight of an antioxidant;
[0112] 0.8 parts by weight of a lubricant;
[0113] 4 parts by weight of a toughening agent;
[0114] 0.1 parts by weight of sulfonate flame retardant;
[0115] 0.4 parts by weight of an anti-drip agent;
[0116] 2 parts by weight of an anti-UV agent;
[0117] The polycarbonate polymer consists of high molecular weight aromatic polycarbonate, low molecular weight aromatic polycarbonate and aliphatic polycarbonate, and the weight ratio thereof is 3.5:5:1.5; the weight average molecular weight of the high molecular weight aromatic polycarbonate is 50,000, and the FB2560 polycarbonate material of Saudi Basic Chemicals Company is adopted; the weight average molecular weight of the low molecular weight aromatic polycarbonate is 23,000, and the melt index at 300° C. and 1.2 kg is 9 g / 10 min, and the A1105 polycarbonate product of Wanhua Chemical Group Co., Ltd. is adopted; the weight average molecular weight of the aliphatic polycarbonate is 35,000, and the polypropylene carbonate resin of Changchun Institute of Applied Chemistry is adopted; the antioxidant is the antioxidant RIANOX 245; the lubricant is the silicone lubricant FEIDIAN GM-3200; the toughening agent is composed of equal weights of MMA-grafted cross-linked silicone acrylate (the brand of Guangzhou Energetic Innovation Materials Co., Ltd. is LP2088) and an acrylate graft copolymer with a core-shell structure (KANE of Hangzhou Zhongju Chemical FM-40); the sulfonate flame retardant is potassium benzenesulfonylbenzenesulfonate; the anti-dripping agent is polytetrafluoroethylene powder; the anti-UV agent is composed of equal weights of benzotriazole anti-UV agent and triazine (HPT) anti-UV agent.
[0118] Example 8
[0119] This embodiment provides a polycarbonate composite material for a 5G base station, which is composed of the following components in parts by weight:
[0120] 95 parts by weight of a polycarbonate polymer;
[0121] 0.3 parts by weight of an antioxidant;
[0122] 0.8 parts by weight of a lubricant;
[0123] 4 parts by weight of a toughening agent;
[0124] 0.1 parts by weight of sulfonate flame retardant;
[0125] 0.4 parts by weight of an anti-drip agent;
[0126] 2 parts by weight of an anti-UV agent;
[0127] The polycarbonate polymer consists of high molecular weight aromatic polycarbonate, low molecular weight aromatic polycarbonate and aliphatic polycarbonate, and the weight ratio thereof is 3.5:5:1.5; the weight average molecular weight of the high molecular weight aromatic polycarbonate is 50,000, and the FB2560 polycarbonate material of Saudi Basic Chemicals Company is adopted; the weight average molecular weight of the low molecular weight aromatic polycarbonate is 23,000, and the melt index at 300° C. and 1.2 kg is 9 g / 10 min, and the A1105 polycarbonate product of Wanhua Chemical Group Co., Ltd. is adopted; the weight average molecular weight of the aliphatic polycarbonate is 10,000, and the polypropylene carbonate resin of Changchun Institute of Applied Chemistry is adopted; the antioxidant is the antioxidant RIANOX 245; the lubricant is the silicone lubricant FEIDIAN GM-3200; the toughening agent is composed of equal weights of MMA-grafted cross-linked silicone acrylate (the brand of Guangzhou Energetic Innovation Materials Co., Ltd. is LP2088) and an acrylate graft copolymer with a core-shell structure (KANE of Hangzhou Zhongju Chemical FM-40); the sulfonate flame retardant is composed of potassium benzenesulfonylbenzenesulfonate and potassium perfluorobutylsulfonate, with a weight ratio of 1:1.5; the anti-dripping agent is polytetrafluoroethylene powder; the anti-UV agent is composed of equal weights of benzotriazole anti-UV agent and triazine (HPT) anti-UV agent.
[0128] The applicant prepared the polycarbonate composite material in the above embodiment according to a similar method. Specifically, the polycarbonate polymer, antioxidant, lubricant, sulfonate flame retardant, anti-dripping agent and anti-UV agent were mixed in a mixer and added to a twin-screw extruder. Eight test samples were obtained by melt extrusion, namely, sample 1 to sample 8 (corresponding to embodiment 1 to embodiment 8, respectively). The obtained samples were tested. The test method and test results are shown as follows:
[0129] Tensile properties: tested according to ISO 527 standard, tensile speed is 50mm / min;
[0130] Bending strength: tested according to ISO 178 standard, bending speed is 2mm / min;
[0131] Notched impact strength: tested according to ISO 180 / 1A standard, sample thickness is 4.0mm;
[0132] Xenon lamp aging performance: tested according to ISO 4892-2:2013 cycle 1 standard, 1000H;
[0133] The specific test results are shown in Table 1 below.
[0134] Table 1 Performance test results
[0135] Tensile strength / MPa Bending strength / MPa <![CDATA[Notched impact strength / (kJ / m 2 )]]> △E Example 1 66 92 72 1.7 Example 2 63 90 62 1.9 Example 3 62 94 56 1.6 Example 4 56 89 65 2.4 Example 5 65 86 68 2.2 Example 6 65 89 50 1.8 Example 7 66 88 67 2.8 Example 8 62 84 64 2.1
[0136] It can be seen from the above experimental results that in the present invention, by adjusting the composition and ratio of the polycarbonate material in the composite material, and optimizing the flame retardant, anti-UV agent, etc., the prepared polycarbonate composite material is comprehensively improved in terms of tensile strength, flexural strength, impact strength, and anti-aging performance. In addition, the applicant also conducted a thermal deformation test on the PC alloy material in the above embodiment. The thermal deformation temperature of all materials is basically 120°C or above, and can be widely used in harsh high-temperature outdoor environments. Moreover, the content of auxiliary components in the entire material formula system does not exceed 10wt%. The composite material retains the characteristics of the polycarbonate itself as much as possible while achieving the above-mentioned modification, so that the composite material can be widely used in fields such as 5G base stations.
[0137] The above is only an exemplary embodiment of the present disclosure, and the scope of the present disclosure cannot be limited thereto. That is, any equivalent changes and modifications made according to the teachings of the present disclosure are still within the scope of the present disclosure. After considering the specification and practicing the disclosure here, those skilled in the art will easily think of the implementation scheme of the present disclosure. The present invention is intended to cover any variation, use or adaptive change of the present disclosure, which follows the general principles of the present disclosure and includes common knowledge or customary technical means in the technical field not recorded in the present disclosure. The description and examples are regarded as exemplary only, and the scope and spirit of the present disclosure are defined by the claims.
Claims
1. A polycarbonate composite material for a 5G base station, characterized in that: It consists of the following components in parts by weight: 90-95 parts by weight of a polycarbonate polymer; 0.2-0.4 parts by weight of an antioxidant; 0.5 to 1.0 parts by weight of a lubricant; 3.0 to 5.0 parts by weight of a toughening agent; 0.05-0.2 parts by weight of sulfonate flame retardant; 0.3-0.5 parts by weight of an anti-dripping agent; 1.0 to 3.0 parts by weight of an anti-UV agent; The polycarbonate polymer comprises high molecular weight aromatic polycarbonate and aliphatic polycarbonate, the content of the high molecular weight aromatic polycarbonate in the polycarbonate polymer is not less than 30wt%; the weight average molecular weight of the high molecular weight aromatic polycarbonate is not less than 25,000.
2. The polycarbonate composite material according to claim 1, characterized in that: The weight average molecular weight of the high molecular weight aromatic polycarbonate is 30,000 to 52,000.
3. The polycarbonate composite material according to claim 1, characterized in that: The weight average molecular weight of the aliphatic polycarbonate is 20,000-60,000.
4. The polycarbonate composite material according to any one of claims 1 to 3, characterized in that: The polycarbonate polymer further includes low molecular weight aromatic polycarbonate, the weight average molecular weight of the low molecular weight aromatic polycarbonate is not higher than 30,000; preferably, the weight average molecular weight of the low molecular weight aromatic polycarbonate is 20,000-30,000.
5. The polycarbonate composite material according to claim 4, characterized in that: The low molecular weight aromatic polycarbonate has a melt index of 7 to 13 g / 10 min at 300° C. and 1.2 kg.
6. The polycarbonate composite material according to claim 4, characterized in that: The weight ratio of the high molecular weight aromatic polycarbonate, the low molecular weight aromatic polycarbonate and the aliphatic polycarbonate is (3-4):5:(0.5-2).
7. The polycarbonate composite material according to claim 4, characterized in that: The toughening agent is MMA-grafted cross-linked silicone acrylate.
8. The polycarbonate composite material according to claim 4, characterized in that: The anti-UV agent is a composite of a benzotriazole anti-UV agent and a triazine anti-UV agent in equal weights.
9. The polycarbonate composite material according to claim 4, characterized in that: The sulfonate flame retardant is selected from one or more of potassium benzenesulfonylbenzenesulfonate, potassium perfluorobutylsulfonate, and sodium 2,4,5-trichlorobenzenesulfonate.
10. The method for preparing a polycarbonate composite material according to any one of claims 1 to 9, characterized in that: The method comprises the following steps: mixing the polycarbonate polymer, antioxidant, lubricant, sulfonate flame retardant, anti-dripping agent and anti-UV agent in a mixer, adding the mixture into a twin-screw extruder, and performing melt extrusion to obtain the product.
Citation Information
Patent Citations
Polycarbonate resin composition and molded body, film, plate and injection-molded article obtained by molding same
CN102656231A
Polycarbonate composite material and preparation method thereof
CN104761878A
Resin composition, cured molded article, fiber-reinforced plastic molding material, fiber-reinforced plastic, fiber-reinforced plastic laminated molded body, and methods for producing same
CN113613878A